Assessing the impact of common bile duct resection in the surgical management of gallbladder cancer. Issue 2 (20th May 2016) - Gani, Faiz; Buettner, Stefan; Margonis, Georgios A.; Ethun, Cecilia G.; Poultsides, George; Tran, Thuy; Idrees, Kamran; Isom, Chelsea A.; Fields, Ryan C.; Krasnick, Bradley; Weber, Sharon M.; Salem, Ahmed; et al.
Abstract : Background: Although radical re‐resection for gallbladder cancer (GBC) has been advocated, the optimal extent of re‐resection remains unknown. The current study aimed to assess the impact of common bile duct (CBD) resection on survival among patients undergoing surgery for GBC. Methods: Patients undergoing curative‐intent surgery for GBC were identified using a multi‐institutional cohort of patients. Multivariable Cox‐proportional hazards regression was performed to identify risk factors for a poor overall survival (OS). Results: Among the 449 patients identified, 26.9% underwent a concomitant CBD resection. The median number of lymph nodes harvested did not differ based on CBD resection (CBD, 4 [IQR: 2–9] vs. no CBD, 3 [IQR: 1–7], P  = 0.108). While patients who underwent a CBD resection had a worse OS, after adjusting for potential confounders, CBD resection did not impact OS (HR = 1.40, 95%CI 0.87–2.27, P  = 0.170). Rather, the presence of advanced disease (T3: HR = 3.11, 95%CI 1.22–7.96, P  = 0.018; T4: HR = 7.24, 95%CI 1.70–30.85, P  = 0.007) and the presence of disease at the surgical margin (HR = 2.58, 95%CI 1.26–5.31, P  = 0.010) were predictive of a worse OS. Conclusions: CBD resection did not yield a higher lymph node count and was not associated with an improved survival. Routine CBD excision in the re‐resection of GBC is unwarranted and should only be performed selectively. J. Surg. Oncol. 2016;114:176–180 . © 2016 Wiley Periodicals, Inc.